In-depth analysis of cis-determinants that either promote or inhibit reinitiation on GCN4 mRNA after translation of its four short uORFs - Gunišová, Stanislava; Beznosková, Petra; Mohammad, Mahabub Pasha; Vlčková, Vladislava; Valášek, Leoš Shivaya (RNA (New York, N.Y.), 2016)
Translational control in eukaryotes is exerted by many means, one of which involves a ribosome translating multiple cistrons per mRNA as in bacteria. It is called reinitiation (REI) and occurs on mRNAs where the main ORF is preceded by a short upstream uORF(s). Some uORFs support efficient REI on downstream cistrons, whereas some others do not. The mRNA of yeast transcriptional activator GCN4 contains four uORFs of both types that together compose an intriguing regulatory mechanism of its expression responding to nutrients' availability and various stresses. Here we subjected all GCN4 uORFs to a comprehensive analysis to identify all REI-promoting and inhibiting cis-determinants that contribute either autonomously or in synergy to the overall efficiency of REI on GCN4. We found that the 3' sequences of uORFs 1-3 contain a conserved AU1-2A/UUAU2 motif that promotes REI in position-specific, autonomous fashion such as the REI-promoting elements occurring in 5' sequences of uORF1 and uORF2. We also identified autonomous and transferable REI-inhibiting elements in the 3' sequences of uORF2 and uORF3, immediately following their AU-rich motif. Furthermore, we analyzed contributions of coding triplets and terminating stop codon tetranucleotides of GCN4 uORFs showing a negative correlation between the efficiency of reinitiation and efficiency of translation termination. Together we provide a complex overview of all cis-determinants of REI with their effects set in the context of the overall GCN4 translational control.
Keywords: sekvenční analýza RNA; Saccharomyces cerevisiae Proteins; RNA, Messenger; regulace genové exprese u hub; sekvence nukleotidů; iniciace translace peptidového řetězce; transkripční faktory bZIP; Saccharomyces cerevisiae; GCN4; cis-regulation; translational control; Basic-Leucine Zipper Transcription Factors; otevřené čtecí rámce; Gene Expression Regulation, Fungal; Saccharomyces cerevisiae - proteiny; Open Reading Frames; Peptide Chain Initiation, Translational; Base Sequence; Sequence Analysis, RNA; uORF; reinitiation; messenger RNA